Perceived Causes of Students’ Poor Performance in Mathematics: A Case Study at Ba and Tavua Secondary Schools - Chand, Samlesh; Chaudhary, Kaylash; Prasad, Avinesh; Chand, Vishal (Frontiers in Applied Mathematics and Statistics, 2021)
Poor achievement in mathematics is an issue of great concern for many countries across the globe. Fiji is one of the countries in the South Pacific experiencing the same trends, pressures, and concerns. This study aims to seek the views of stakeholders (students, teachers, heads of departments, and school heads) with regards to the causes of poor achievement in mathematics at the senior grades of secondary schools in the districts of Ba and Tavua, Fiji. A descriptive design using both quantitative and qualitative approaches were utilized whereby data were collected from 201 upper secondary school respondents comprising 171 students, 16 mathematics teachers, 7 department heads, and 7 school heads from seven randomly selected schools in the districts of Ba and Tavua. The study found that the students had a negative attitude toward mathematics. It was also found that an ineffective mathematics curriculum in secondary schools was the reason behind poor performance in the subject. Moreover, many of the primary school teachers lacked potential and competence to teach mathematics at primary school levels, and this largely contributed toward the lack of interest amongst students, hence translating into poor achievement at both upper and lower secondary levels. On the other hand, however, it was gathered that secondary school teachers were rather positive, good quality, performing, and fully qualified as far as the teaching of mathematics and delivery of the subject matter was concerned. Review and amendments to the year 12 and 13 mathematics curriculum, use of technologies to teach mathematics, improving the quality of primary school mathematics teachers, reducing the emphasis on exams, introducing internal assessments, projects, and field work in the mathematics curriculum were a few of the significant recommendations made from this study.